General Characteristics of Eyelid Skin Morphological Alterations in Aging - Alexandrovna, Yutskovskaya Yana (Asian Journal of Pharmaceutics (AJP), 2018)
Aim of the Investigation: Nowadays, eyelid skin is found to be subject to the destructive alterations well before than other facial areas. Skin restructuring changes, wherein lie visible signs of aging onset, are known to involve all the elements - epidermis, dermis, and subcutaneous deep tissues. Morphological skin condition estimation in females of different age groups based on the set of signs. Materials and Methods: Eyelid skin alteration comprehensive analysis has been conducted, taking into account patientâ€™s age, phototype, and aging morphological type. 60 females of three different photo- and morphotypes in three age groups have been examined: 20 females were 25â€“44 aged; 20â€“45â€“59 aged, and 20â€“60â€“74 aged. To examine structural and biochemical alteration in the skin tissues of the upper eyelid histological and immunohistological dyeing methods have been applied. The material has been statistically processed with the software package program â€œstatgraphics.â€ Results and Discussion: Skin structural elements alterations in women are associated with the age, photo- and morphotype. Distinct skin structures are affected by the different factors. Starting at the age of 45â€“59 destructive eyelid skin alterations are dominating. Third skin phototype appeared to be the most sustainable toward aging. Each morphological aging type is contributing to the skin element alterations.